Developing Antenatal Education in Preparation for Motherhood - A Participatory Action Research Approach - BRADY, VIVIENNE; LALOR, JOAN; MURPHY-LAWLESS, JO (My University, 2011)
Antenatal education (ANE) is offered in maternity hospitals in Ireland with the premise that it prepares women for birth and motherhood . There is evidence to suggest however, that current ANE programmes do not reflect women ?s expectations and needs . This research is focused on working towards developing antenatal education that is grounded in the felt needs and life experiences of women , with a view to supporting women?s decision - making processes, and understanding of pregnancy, birth and early motherhood . Until now, general planning and development of maternity care services in Ireland ha ve involved minimal consultation with women as service users. Dialogue and active participation with women and antenatal educators to develop ANE is a significant focus of this study . A Participatory Action Research (PAR) approach is used informed by the conviction that all individuals have the right to actively contribute to the democratic development of policies and processes that affect them .
ICM 29th Triennial Congress
PRESENTED
Durban, South Africa
Keywords: Antenatal Education